2020
DOI: 10.3889/oamjms.2020.5447
|View full text |Cite
|
Sign up to set email alerts
|

An Iodine Treatments Effect on Cell Proliferation Rates of Breast Cancer Cell Lines; In Vitro Study

Abstract: BACKGROUND: Iodine can reduce breast tumor progression by mediates an antiproliferative effect. AIM: This study aimed to investigate the effect of iodine (I2), Lugol (I3K), and the combination of both on cell proliferation of three different types of breast cancer cell lines. METHODS: The samples were MCF7, SKBR3, and MDA-MB 213 cell lines. Cell proliferation rate was measured using colorimetric and clonogenic assays. RESULTS: The cell proliferation rate of MDA-MB 231 cells was reduced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…In previous studies, iodine has shown an Inhibition Concentration 50% (IC50) in the low micromolar range, marking its potential to be developed as a new anticancer drug. However, the dose should certainly be lowered again, as lower doses will help reduce the appearance of unwanted side effects (Elliyanti et al, 2020). Iodine turns out to have an important role in influencing the biological process in breast cancer, because the consumption of large amounts of iodine will help cure breast cancer gradually.…”
Section: Invitromentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, iodine has shown an Inhibition Concentration 50% (IC50) in the low micromolar range, marking its potential to be developed as a new anticancer drug. However, the dose should certainly be lowered again, as lower doses will help reduce the appearance of unwanted side effects (Elliyanti et al, 2020). Iodine turns out to have an important role in influencing the biological process in breast cancer, because the consumption of large amounts of iodine will help cure breast cancer gradually.…”
Section: Invitromentioning
confidence: 99%
“…NIS protein expression can be detected in breast cancer cells with varying degrees in the cytoplasm and cell membrane. It transports iodine into the cell, and it be suggested as a new adjuvant treatment for breast cancer (Elliyanti et al, 2016, Elliyanti et al,2020. Improving iodine intake in cancer patients will potentially reduce the likelihood of tumor progression so that the body needs to meet daily iodine requirements (Winder et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…NIS is a transmembrane glycoprotein that contains 13 membrane-spanning segments and three N-linked carbohydrates. It resides in the basolateral membrane of epithelial thyroid cells [16][17][18][19][20]. Besides the thyroid cell, NIS is expressed by extra-thyroid tissues [20].…”
Section: Transport Radioiodinementioning
confidence: 99%